Relationships Between Functionality, Depression, and Anxiety With Community Integration and Quality of Life in Chronic Traumatic Spinal Cord Injury. (3rd September 2021) - García-Rudolph, Alejandro; Cegarra, Blanca; Opisso, Eloy; Tormos, Josep María; Saurí, Joan
Abstract : Supplemental digital content is available in the text. Abstract : Objectives: The aims of the study were (1) to identify relationships between functional and psychological aspects with community integration and quality of life assessments in people with chronic traumatic spinal cord injury and (2) to analyze clinical and demographic predictors of quality of life dimensions. Design: This is an observational cohort study, and correlation coefficients were calculated between the Functional Independence Measure, the Hospital Anxiety and Depression Scale, the Community Integration Questionnaire, and the World Health Organization Quality of Life–BREF dimensions (physical [D1], psychological [D2], social [D3], and environmental [D4]). Quality of life predictors were identified using multiple linear regression analyses. Results: Nine hundred seventy-five people with traumatic spinal cord injury assessed since 2007–2020 were included. The Community Integration Questionnaire home integration correlated strongly with the Functional Independence Measure self-care ( r = 0.74) and transfers ( r = 0.62) for participants with tetraplegia. The specific Hospital Anxiety and Depression Scale items (known as the anhedonia subscale) correlated strongly with D1 ( r = −0.65), D2 ( r = −0.69), D3 ( r = −0.53), and D4 ( r = −0.51) for participants with paraplegia and D1 ( r = −0.53), D2 ( r = −0.61), D3 ( r = −0.47), and D4 ( r = −0.53) for participants with tetraplegia. The Hospital Anxiety and Depression Scale–depression was the most relevant predictor of D1 (β = −0.61) and D2 (β = −0.76). Conclusions: The Functional Independence Measure transfers and self-care were strongly associated with the Community Integration Questionnaire home integration (in participants with tetraplegia). Anhedonia was strongly related to all four World Health Organization Quality of Life–BREF Scale dimensions, being the Hospital Anxiety and Depression Scale–depression the most relevant predictor of D1 and D2. To Claim CME Credits: Complete the self-assessment activity and evaluation online at http://www.physiatry.org/JournalCME CME Objectives: Upon completion of this article, the reader should be able to (1) Determine the associations between functional and psychological measures with community integration domains and quality of life from a multidimensional perspective (physical, psychological, social, and environmental) in persons with chronic traumatic paraplegia or tetraplegia living in the community; (2) Identify long-term clinical and demographic predictors of specific quality of life dimensions (e.g., physical and psychological) in persons with paraplegia or tetraplegia living in the community; and (3) Illustrate the strength of the identified associations and the impact of the quality of life predictors to suggest possible specific aspects to be addressed by professionals in clinical practice. Level: Advanced Accreditation: The Association of Academic Physiatrists is accredited by the Accreditation Council for Continuing Medical Education to provide continuing medical education for physicians. The Association of Academic Physiatrists designates this Journal-based CME activity for a maximum of 1.0 AMA PRA Category 1 Credit(s) ™. Physicians should only claim credit commensurate with the extent of their participation in the activity.